Caracterização e efeitos das tecnologias na sustentabilidade da pecuária leiteira familiar no semi-árido sergipano - Carvalho, Evelyne Costa (2008)
The cattle milkmaid is present in almost the small totality of the e average familiar properties, representing the biggest participation in the composition of the rude value of national production of familiar agriculture. Especially in the half-arid region northeastern the milk production is distinguished as main economic activity, which possesss great technological and legal challenges to be surpassed. In this direction, one becomes necessary to promote the action accomplishment aiming at the sustainable development of familiar agriculture, contemplating its technological, productive, educative, ambient dimensions and of social organization, by means of the generation and diffusion of suitable technologies to the regional especificidades, also the emergent sector of assentaments of agrarian reform. Lined up with this vision, the present study she aimed at to contribute with the improvement of the quality of the milk produced in assentament of agrarian reform of the half-arid of Sergipe, through participative research of technologies and the use of the Embrapa s kit of milks manual ®. It was gotten as resulted significant, had been identified to a roll of 16 indicators of sustainability of agro ecosystems Cattle milkmaid practised in the assentament of Nossa Senhora da Boa Hora, half-arid of Sergipe , and mainly it was inquired that the use of the Embrapa s kit of milks manual ® contributed to adjust the milk produced in the Assentament to the legal requirements, observing a reduction in the somatic frame number in milk. In such a way, the biggest adoption of sustainable, appropriate technologies for the familiar farmers, the maintenance propitiates quality of production better thus allowing/formal insertion of these producers in the market.